Pharmacokinetic/Pharmacodynamic Adequacy of Novel β-Lactam/β-Lactamase Inhibitors against Gram-Negative Bacterial in Critically Ill Patients - Ruiying Han; Dan Sun; Sihan Li; Jiaojiao Chen; Mengmeng Teng; Bo Yang; Yalin Dong; Taotao Wang (MDPI AG, 2021)
The optimal regimens of novel β-lactam/β-lactamase inhibitors (BLBLIs), ceftazidime/avibactam, ceftolozane/tazobactam, and meropenem/vaborbactam, are not well defined in critically ill patients. This study was conducted to identify optimal regimens of BLBLIs in these patients. A Monte Carlo simulation was performed using the published data to calculate the joint probability of target attainment (PTA) and the cumulative fraction of response (CFR). For the target of β-lactam of 100% time with free drug concentration remains above minimal inhibitory concentrations, the PTAs of BLBLIs standard regimens were <90% at a clinical breakpoint for Enterobacteriaceae and Pseudomonas aeruginosa. For ceftazidime/avibactam, 2000 mg/500 mg/8 h by 4 h infusion achieved >90% CFR for Escherichia coli; even for 4000 mg/1000 mg/6 h by continuous infusion, CFR for Klebsiella pneumoniae was <90%; the CFRs of 3500 mg/875 mg/6 h by 4 h infusion and 4000 mg/1000 mg/8 h by continuous infusion were appropriate for Pseudomonas aeruginosa. For ceftolozane/tazobactam, the CFR of standard regimen was >90% for Escherichia coli, however, 2000 mg/1000 mg/6 h by continuous infusion achieved <90% CFRs for Klebsiella pneumoniae and Pseudomonas aeruginosa. For meropenem/vaborbactam, standard regimen achieved optimal attainments for Escherichia coli and Klebsiella pneumoniae; 2000 mg/2000 mg/6 h by 5 h infusion, 2500 mg /2500 mg/6 h by 4 h infusion, 3000 mg/3000 mg/6 h by 3 h infusion and 4000 mg/4000 mg/8 h by 5 h infusion achieved >90% CFRs for Pseudomonas aeruginosa. The CFRs of three BLBLIs were similar for Escherichia coli, but meropenem/vaborbactam were superior for Klebsiella pneumoniae and Pseudomonas aeruginosa.